Pengaruh Durasi Penggunaan Sosial Media Terhadap Kejadian Insomnia Mahasiswa - Irawati Irawati; Kistan Kistan; Muhammad Basri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Sleep is a physiological need that must be fulfilled by every human being for at least eight to 10 hours every day. The use of social media in uncontrolled time and duration can interfere with the quality and quantity of sleep-in students. This study aims to determine the relationship between the duration of social media use and the incidence of insomnia in Batari Toja Nursing Academy students. The method used in this study was an analytical survey with a cross sectional approach using total sampling technique obtained as many as 297 respondents. Data collection was carried out using a questionnaire via google form which was distributed using a link to each class whtassapp group. Data were analysed bivariately using the spearman correlation test. Results: the study showed that there was a strong relationship with a positive and significant direction between the duration of social media use and the incidence of insomnia in students of Batari Toja Nursing Academy (p value = 0.00 <0.05, with a value of r = 0.739). It is hoped that students can manage their time using social media, reduce and avoid using social media at night before sleep